Sosialisasi Digital Marketing Pada UMKM Desa Jatimekar Jatiluhur Purwakarta - Sawitri Rahayu, Julianti; Fahrizal, Mohammad; Rahmayanti, Siska; Oktapianti, Mila Sari (STIE Syariah Indonesia Purwakarta, 2022)
Information Technology has a very important role as a solution to overcome government affairs, one of which is business and the economy. The presence of the marketplace now helps a lot of people's needs, how much activity is spent using the marketplace as a fulfillment of daily needs. MSME actors are required to be able to adapt to current transaction conditions and developments. The purpose of this PKM program is so that MSME actors in Jatiluhur Village, Jatiluhur Purwakarta, can increase the number of sales through digital marketing, and MSME actors can adapt to new habits, namely digital marketing. The method used in this PKM uses a lecture and discussion approach. The results of PKM activities regarding digital marketing socialization to MSMEs in Jatimkar Village, Jatiluhur District, Purwakarta Regency went smoothly, it was seen that MSME actors were very enthusiastic about the presentation of digital marketing materials and training. This activity has a positive impact on MSME actors, one of which is increasing the knowledge and understanding of MSME actors about digital marketing and increasing confidence in marketing products online